Empowering Rural Communities: Smart English Home Ignites Opportunities in Sungai Alam Village, Bengkalis Island - Putra, Halim Dwi; Sukma, Doris; Sabri, Muhammad (Devotion: Journal Corner of Community Service, 2023)
This servitude 2023 explores the impact of the Smart English Home initiative in Sungai Alam Village, Bengkalis Island, aiming to empower rural communities through English language education. The study investigates the potential opportunities ignited by this program, focusing on the enhancement of educational access, economic prospects, and community development. By examining the implementation of the Smart English Home, the research aims to provide insights into the transformative effects of language empowerment in rural settings, contributing to the broader discourse on rural community development and empowerment initiatives. This abstract synthesizes the potential impact of the Smart English Home initiative in Sungai Alam Village, Bengkalis Island, emphasizing its role in empowering rural communities through English language education and its broader implications for community development and economic prospects.